2003
DOI: 10.1097/01.prs.0000053549.45063.a1
|View full text |Cite
|
Sign up to set email alerts
|

Low-Molecular-Weight Heparin (Dalteparin) Effectively Prevents Thrombosis in a Rat Model of Deep Arterial Injury

Abstract: Unfractionated heparin is often used to prevent thrombosis in microvascular surgery, but a major drawback of heparin therapy is increased bleeding. Low-molecular-weight heparins prevent venous thrombosis as effectively as heparin and have better bioavailability and a longer plasma half-life, which explains the increased use of low-molecular-weight heparins as substitutes for heparin in clinical practice. However, the ability of low-molecular-weight heparins to prevent arterial thrombosis has been debated. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Although some studies clearly have found LMWH to be a less effective treatment than traditional heparin in reducing the frequency of arterial thrombosis, 46,47 others have reported better or equal results. 34,48 In a rabbit model Zhang et al 48 observed a 50% increase in the patency of arterial anastomoses with LMWH in comparison with no anticoagulation, but observed no difference in the patency of small venous anastomoses.…”
Section: Low Molecular Weight Heparinsmentioning
confidence: 96%
See 3 more Smart Citations
“…Although some studies clearly have found LMWH to be a less effective treatment than traditional heparin in reducing the frequency of arterial thrombosis, 46,47 others have reported better or equal results. 34,48 In a rabbit model Zhang et al 48 observed a 50% increase in the patency of arterial anastomoses with LMWH in comparison with no anticoagulation, but observed no difference in the patency of small venous anastomoses.…”
Section: Low Molecular Weight Heparinsmentioning
confidence: 96%
“…In addition to causing fewer hematomas LMWH has higher bioavailability (85% compared with 10%), a longer plasma half-life, a steady dose-response relationship, 34,49 and causes fewer cases of thrombocytopenia compared with unfractionated heparin. 25,50,51 Thus LMWH produces reliable anticoagulation over a longer period of time without the need for monitoring.…”
Section: Low Molecular Weight Heparinsmentioning
confidence: 98%
See 2 more Smart Citations
“…Experimental studies in rats have demonstrated better results on prevention of microanastomosis thrombosis using LMWH, but often with a dose greater than the typical human dose. 28,29 We observed that de 0.5 mg/kg/day dosage of enoxaparin (similar that used in prophylaxis of thromboembolism in adult human, 40 mg/day) was not adequate to prevent thrombosis in femoral vein microanastomosis in rats.…”
Section: Discussionmentioning
confidence: 91%